ANALISIS PENDEKATAN BALANCED SCORECARD MENGUKUR KINERJA PERUSAHAAN - Tasman H. Taher (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2018)
To the face the increase of the current business environment  into a more complex situation, a method of performance measurement       that                  can accurately and comprehensively assess   the company's performance is essentially needed. In this case the method which can be used is the Balanced Scorecard. The objective of the Balanced Scorecard method is to measure the performance of the company from four perspectives, namely:  learning  and  growth  perspective,   internal   business  process  perspective, customer perspective and financial perspective.The researcher conducted the research on PLN Palangka Raya District using the data from  2006-2008 to analyze the financial perspective, while for other perspectives using company data and calculation of questionnaires distributed to employees of PLN Palangka Raya District.The results  of  the  research  reveals  that  the  overall  performance  of  PLN Palangka Raya  District  is  good  enough,  it  is  indicated  by  the  value  generated  from  the respective scorecards of  each perspective. The conclusion that can be derived through the  analysis  is  that  the  Balanced  Scorecard  is  the  best  method  in  assessing  the performance of the company, since the Balanced Scorecard raises the important aspects that are ignored by the traditional performance measurement, such as aspects of human resources, systems used in a corporation, operational processes, and aspects of customer satisfaction, so that the measurement results of the Balanced Scorecard is more accurate. Accurate  performance  measurement  is  very  important  for  management,  both  in  the process of  planning, decision making, and controlling, and in realizing the vision and mission of the corporation.